Contribution to the study of arrenuroid water mites (Acari: Hydrachnidia) from Turkey - Esen, Yunus; Erman, Orhan; Dilkaraoglu, Sibel (Magnolia Press, 2013)
In this paper, one new water mite species of the genus Arrenurus, i.e. Arrenurus (s.str.) ovatipetiolatus Esen & Erman sp. nov. and some new records for the Turkish fauna are given. The first description of the female of Arrenurus (s.str.) antalyensis Gulle, Boyaci & Gulle, 2011 is given. Arrenurus (s.str.) kermanensis Pesic, Smit & Asadi, 2011, which is only known from type locality in Iran, and reported here, is new record for the Turkish fauna, is redescribed. Arrenurus (s.str.) kurui Erman, 1993 is considered a junior synonym of Arrenurus (s.str.) vavrai Thon, 1899. Krendowskia (s.str.) levantensis Smit, 1997, a species only known from Israel and Iran, is reported first time from Turkey.
Keywords: water mite; new species; Arrenurus; Krendowskia; Turkey